ANALISIS PELAKSANAAN PEMBELAJARAN GEOGRAFI SECARA DARING DIMASA PANDEMI COVID-19 SMA NEGERI 6 PONTIANAK - Sri Maulani Utami; Sulistyarini Sulistyarini; Nur Meily Adlika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this study is to find out the process of implementing geography learning onlineduring the Pandemic Covid-19 at SMA Negeri 6 Pontianak. The method of this study isdescriptive in the form of qualitative approach. The sources of data in this study were twogeography teachers at SMA Negeri 6 Pontianak. The data collection technique of this studywas observation, interview, and documentation . The results of the study show the followingfindings: (1) Planning for geography learning during the Pandemic Covid-19 , namely bypreparing a Learning Implementation Plan that has been adjusted to the syllabus. (2) Theprocess of implementing geography learning during the Covid-19 learning activities areimplemented oriented towards student activities carried out using an online system with theGoogle Classroom application (3) he evaluation of learning uses the assessment of attitudes,knowledge and skills (4) The obstacle for teachers in learning geography during the Covid-19 Pandemic was the lack of facilities and infrastructure that support online lessons.Theconclusion of this study is that the implementation of learning carried out at SMA Negeri 6Pontianak during the Covid-19 Pandemic has been carried out online, with teachers stillmaking customized learning tools.Keywords: Planning, implementation, evaluation, and learning barriers